The Role of The Church In The Education of The Congregation or People To Influence The Surrounding Community - Bernard Lubis; Yulius Enisman Harefa (LPPM IAKN Tarutung, 2022)
Society is a group of people consisting of several humans. In society, Indonesia has six religions, namely Protestant Christianity, Catholicism, Hinduism, Buddhism, Confucianism and Islam. Of these religions have different ways of worshiping or worshiping and also have different reinforcement of faith. As five people who believe in the existence of a Christian God worship the Lord Jesus in the church. The church opens the building that we see where we worship but the church is the person or the church is ourselves. The foundation of Christian faith comes from the Bible which is the source of strength. So the Church must continue to take part in education in order to be able to carry out its greater role in society. The church must also be a place to educate and a place to be educated.